Being a mother of preterm multiples in the context of socioeconomic disadvantage: perceived stress and psychological symptoms - Baptista, Joana (2018)
Objective: This study aimed to examine the differences between mothers of preterm multiples and mothers of preterm singletons in perceived stress and maternal psychological symptoms, and to explore the putative adverse amplified effect of socioeconomic disadvantage. Method: Ninety-five mothers of one-year-olds born preterm participated in this cross-sectional study. Data collection was carried out in two public hospitals from Northern Portugal. To assess maternal perceived daily stress and psychological symptoms, mothers completed two questionnaires. Mothers reported on socioeconomic factors, including family poverty, parent unemployment and low education, and two groups of family socioeconomic disadvantage were created. A child medical risk index was calculated. Results: Results indicated that mothers of preterm multiples reported higher levels of stress than mothers of preterm singletons. Moreover, and specifically regarding psychological functioning, mothers of preterm multiples reported more symptoms than mothers of preterm singletons, but only when living in a context of socioeconomic adversity. Conclusions: The results of the present study have important implications for practice. Mothers of preterm multiples are at higher risk to present mental health difficulties, in comparison to mothers of singletons, especially when exposed to socioeconomic adversities. The development of psychosocial intervention programs and public policies are of decisive importance in helping mothers of multiples adjusting to parenthood.